Mechanical and Tribological Performance of Luffa cylindrica Fibre-Reinforced Epoxy Composite - Niharika Mohanta; Samir Kumar Acharya (BioResources, 2015)
This work focuses on the mechanical properties and solid particle impact behaviour of Luffa cylindrica fibre (LCF)-reinforced epoxy composites. Single (SL)-, double (DL)-, and triple (TL)-layered composites were prepared using the general hand lay-up technique. The erosive wear test was carried out using an air jet erosion tester according to the ASTM G76 standard. The erodent used was silica sand particles (200 ± 50 µm). The experimental parameters studied for the erosion rate of the LCF epoxy composites were impingement angle (30° to 90°) and particle velocity (48 m/s to 82 m/s). Analysis of the results revealed that at the peak erosion rate, semi ductile behaviour of the composite was apparent. Possible erosion mechanisms were discussed and were investigated using scanning electron microscopy (SEM).